VỀ TÍNH LINH ĐỘNG CỦA PHỐI TỬ VÀ CÁC AXIT AMIN VÙNG HOẠT ĐỘNG TRONG CÁC PHỨC AXYL VÀ MICHAELIS CỦA NITROXEFIN VÀ METIXILIN VỚI SAUPBP2A KHÁNG METIXILIN (MRSA) - Vận, Đặng Ứng; Mi, Nguyễn Hoạ; Thành, Trương Nguyện (Vietnam Journal of Chemistry, 2012)
We have implemented 10ns molecular dynamics (MD) calculation for six Michaelis and acyl complexes of antibiotic methicillin (MC1) and nitrocefin (NC1) with Penicillin-binding protein 2a (PBP2a) of Staphylococcus aureus and for apo enzyme as well. The contrary known on the very stable covalent SauPBP2a-β-lactam complexes and the resistance of SauPBP2a has been explained by analyzing structure, dynamics of inhibitor and protein as well. The rearrangement of the helix α2 N-terminus and the strand β3 in active region is not only cause of the resistance. RMSF analyse shown that the flexibility of helix α2 N-terminus, the flexibility of the ligand molecule and Ser403 support significantly the acylation which is more convenience in NC1-complex than in MC1 one. The dynamics of hot-spot residues and the active site adjacent cleft are of particular interest, as they should be suggested to provide additional opportunities for drug discovery that could potentially mitigate the effects of drug resistance.